Thermal performance analysis of PCM building for Moderate climatic region in Bangalore City, India. Issue 1 (1st December 2022) - Kumar, S.; Sheeja, R.; Ajin, M.; Chandrasekar, P.; Sekar, S.; Sai Krishnan, G.S
Abstract: A major percentage of the energy is utilised for the building sectors for cooling the building which is used for Airconditioning systems. One of the techniques for decreasing energy consumption in building systems is passive cooling. The PCM materials was integrated in the building which is isothermal temperature for storing and retrieving the energy during a phase change. The stored PCM is a constant temperature for phase change and also gives the large potential of energy during the storing and releasing energy. The integrated building wall to prevent the solar heat infiltration into buildings and controlling the indoor temperature swing. The selection and efficiency of PCMs are highly subjective to climatic conditions where they applied. In the present study, a real time PCM integrated residential building is studied through numerical simulation using Design Builder software in moderate climatic condition in Bangalore city, India. The result shows that throughout the year, the PCM room does not required any air-conditioning device for cooling application.